Impact of 18F-fluorodeoxyglucose PET/CT in the management of patients with plasma cell disorders. Issue 1 (January 2020) - Shachar, Ben; Prica, Anca; Anconina, Reut; Hawsawy, Asmaa; MacCrostie, Pamela; Langer, Deanna; Metser, Ur
Abstract : Objectives: To evaluate the impact of 18 F-fluorodeoxyglucose PET/CT examinations on the management of patients with plasma cell disorders. Methods: This is a retrospective review of patients in a provincial database with PET/CT performed for plasma cell disorders between 2011 and 2018. The impact of PET/CT on actual patient management and outcome was assessed by two independent readers who compared planned pre-PET/CT management, documented at time of PET/CT requisition, to actual management received through linkages to administrative databases. PET/CT was considered of high impact if it altered the provision of active treatment, changed the modality of treatment or chemotherapy regimen. Change in management and the proportion of patients with high impact PET/CT were assessed. Results: There were 44 patients with plasma cell disorders, including multiple myeloma, solitary plasmacytoma, Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal protein, Skin changes syndrome, or monoclonal gammopathy of undetermined significance or biclonal gammopathy of undetermined significance. Management was altered after 38/56 (67.9%) PET/CT scans. Considering just the initial PET/CT scan in patients who underwent multiple scans, 31/44 (70.5%) patients had their management altered subsequent to PET/CT. Conclusion: PET/CT resulted in a change in planned management in more than two-thirds of patients with plasma cell disorders in the current selected patient cohort. These results should be validated in a larger prospective trial.